ANALISIS KUALITAS SOAL PENILAIAN AKHIR SEMESTER GANJIL KELAS IX MATA PELAJARAN BAHASA INDONESIA DI MTs MANBAUL ULUM BONDOWOSO - Leny Ocktalia; R. Panji Hermoyo; Ali Nuke Affandy (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was intended to describe the quality of the Odd Semester Final Assessment (PAS) for Indonesian Subjects in Class IX MTs ManbaulUlum of Bondowoso in the terms of: 1) cognitive domain level based on KKO (Operational Verb) in the revised edition of Bloom's taxonomy or the development of HOTS questions, and 2) the compatibility of the question with the material, construction and language. The subjects of this research were 50 multiple choice items and the object was the quality of the items. The method used in this research was descriptive qualitative method, because the researcher described the state of the research object/subject. The instruments of this research were documentation and interview method.The results showed that: (1) it was found that 22% met the criteria for developing HOTS questions and 78% were included in the LOTS criteria. It means 11 HOTS questions and 39 LOTS questions.(2) The Semester Final Assessment (PAS) question has one deficiency in the question construction category.The results of the research showed that the subject matter which was formulated was not clear on that one question. Questions and answer choices were not homogeneous and logical. The material and language categories had met the quality standards of the questions. Keywords: HOTS Questions, Quality of PAS Questions, Indonesian Language